SPECIFIC FEATURES OF TRAINING WRESTLING COACHES FOR YOUTH WITH DISABILITIES - Turdiyev To’xtaboy Mamatmurod o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This thesis examines the specific aspects of training coaches to work with young people with disabilities in wrestling. It analyzes the knowledge, skills, and approaches necessary for coaches, considering the diverse needs and characteristics of athletes with disabilities. The thesis outlines the key competencies that should be included in coach training programs, such as adapted training methodologies, safety assurance, inclusive communication, and psychological support. It also discusses the potential of modern information and communication technologies to train coaches and support their professional development.